Treatment of Industrial Water by Nano Technology - shnaihej, Kareem T.; Sukkar, Khalid A.; Basri, Lamya J.; Mohesn, Hasan N. (Journal of Petroleum Research and Studies, 2018)
Nanotechnology: - It is one of the modern scientific achievements where nanotechnology is available, namely the engineering and art of nano scale material treatment (100 nanometers. The ability to manufacture new Nano materials used to treat surface water, groundwater and industrial wastewater contaminated with toxic metal ions, organic and inorganic substances as well as microorganisms. In this research, we discussed the use of Nano materials, or nearby, to remove the dissolved oil pollutants from the industrial wastewater of the South Refinery Company, where we used multitubes of carbon nanotubes. The function of the tubes can be described as a particle filter, Hold large particles of contaminants that are difficult to pass through the tube tunnel). We also used activated carbon powder and carbon filters near pore nanoparticles